2008
DOI: 10.1097/opx.0b013e31817841cb
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Environment of the Optic Nerve Head in Glaucoma

Abstract: The optic nerve head (ONH) is of particular interest from a biomechanical perspective because it is a weak spot within an otherwise strong corneo-scleral envelope. The lamina cribrosa provides structural and functional support to the retinal ganglion cell axons as they pass from the relatively high-pressure environment in the eye to a low-pressure region in the retrobulbar cerebrospinal space. To protect the retinal ganglion cell axons within this unique environment, the lamina cribrosa in higher primates has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
192
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 225 publications
(201 citation statements)
references
References 44 publications
6
192
0
3
Order By: Relevance
“…Much of the field has focused on astrocytes, microglia, and RGCs themselves, with some interest in the endothelial control of blood flow (65)(66)(67). Our demonstration that specific radiation of the eye can prevent glaucoma is an important finding.…”
Section: Figurementioning
confidence: 94%
“…Much of the field has focused on astrocytes, microglia, and RGCs themselves, with some interest in the endothelial control of blood flow (65)(66)(67). Our demonstration that specific radiation of the eye can prevent glaucoma is an important finding.…”
Section: Figurementioning
confidence: 94%
“…Although the proximate cause of early edema is stagnant axonal transport, there still remains some uncertainty about the relative effects of compression and ischemia. [1][2][3] Burgoyne et al 4 and others [5][6][7][8][9][10][11] have proposed a conceptual approach that analyzes the optic nerve head (ONH) as a biomechanical structure. They hypothesize that stress (force/ cross-sectional area) and strain (local deformation) on the ONH may be key determinants of axonal, glial, and vascular dysfunction in the pathogenesis and progression of glaucoma.…”
mentioning
confidence: 99%
“…This implies that if the TOPG increases from the center to the periphery, the fiber bundles of the optic nerve will be compressed. It has been shown that the optic nerve is particularly susceptible to pressure changes and prone to deformation (Crawford Downs et al, 2011;Downs et al, 2008;Sigal et al, 2007). Even though these studies focused on the lamina cribrosa and the scleral canal, it is reasonable to assume that the optic canal is stiffer than the scleral canal.…”
Section: Figure 4 Pressures Around the Optic Nerve (On)mentioning
confidence: 99%